Anisotropic Growth of Nonlayered CdS on MoS2 Monolayer for Functional Vertical Heterostructures. (10th February 2016) - Zheng, Wei; Feng, Wei; Zhang, Xin; Chen, Xiaoshuang; Liu, Guangbo; Qiu, Yunfeng; Hasan, Tawfique; Tan, Pingheng; Hu, Ping An
Abstract : 2D semiconductors have emerged as a crucial material for use in next‐generation optotelectronics. Similar to microelectronic devices, 2D vertical heterostructures will most likely be the elemental components for future nanoscale electronics and optotelectronics. To date, the components of mostly reported 2D van der Waals heterostructures are restricted to layer crystals. In this work, it is demonstrated that nonlayered semiconductors of CdS can be epitaxially grown on to 2D layered MoS2 substrate to form a new quasi vertical heterostructure with clean interface by chemical vapor deposition. Photodetectors based on this CdS/MoS2 heterostructure show broader wavelength response and ≈50‐fold improvement in photoresponsivity, compared to the devices fabricated from MoS2 monolayer only. This research opens up a way to fabricate a variety of functional quasi heterostructures from nonlayered semiconductors. Abstract : A new van der Waals heterostructure consisting of semiconducting CdS nanosheets and MoS2 is epitaxially grown onto a 2D layered crystal via Chemical Vapor Deposition. Photodetectros based on this novel heterostructure show a significant enhancement in photocurrent and photoresponsivity compared to MoS2 photodetectors.